Интеграция картографических данных в единую информационнную систему - Коцаб, М.; Радей, К. (Видавництво Львівської політехніки, 2013)
It is considered one of the most important problem of modern cartography – the integration of various cartographic products into one info rmation system in compliance with INSPIRE requirements and described important role of geodesic sphere in the performance of this integration. Basic rules of integration of geodata users are given and the importance of cadastral data for GIS is underlined. It is emphasized that definition of the reference layer (orthophoto) must comply with ISO standards. More attention must be paid to the uniform presentation of geodata for users within one coherent environment. Розглянуто одну з найважливіших проблем сучасної картографії – інтеграцію різних картографічних творів в одну інформаційну систему згідно із вимогами INSPIRE і важливу роль геодезичної галузі при виконанні цієї інтеграції . Перелічені основні правила інтеграції геоданих і підкреслено важливість кадастрових даних для користувачів ГІС , а також згодом , що дефініція референційного шару ( ортофотокарти ) повинна відповідати нормам ISO. Більше уваг и рекомендовано приділяти одноманітній презентації геоданних для користувачів в одному когерентному середовищі.